PENERAPAN MODEL PEMETAAN KONSEP DALAM PENINGKATAN PEMBELAJARAN BERMAKNA PADA MATA KULIAH LANDASAN PENDIDIKAN - Nuryani, Pupun (PEDAGOGIA, 2015)
This research is motivated by the need for improvements to be made meaningful learning course on educational foundation, background PGSD students level 1 (one) following subjectseducational foundation educational background in high school are usually / almost all have not understood the concept of education, causing some negative things in the implementation of learning, among others, the absence of transactional patterns of learning, and the lack of enthusiasm of students in the following subjects educational foundation. The study was conducted using a mixed method design methodology for quantitative, and qualitative approaches are integrated and support each other, which is the subject of research is PGSD students (1st semester). The results show that through application of models of concept mapping students get meaningful learning this can be seen during the lecture students more communicative, students' ability to master and understand the material more comprehensive and meaningful learning course on Basis of Education can be seen from the test results of pre-test and post-test results test.Berdasarkan findings obtained in the study of the concept mapping model in the improvement of meaningful learning in the subject of Education Platform, some suggestions addressed to thefollowing parties: For the majorsKeywords : Learning Through Concept Mapping Model